HISTOLOGY PERSPECTIVE OF CHILDHOOD RENAL DISEASES- A SINGLE CENTRE EXPERIENCE - Syed Sajid Hussain Shah; Naureen Akhtar (Journal of University Medical & Dental College, 2016)
ABSTRACT: BACKGROUND: There is not much information regarding the prevalence of different renal diseases in paediatric population in Pakistan due to lack of central data. A few studies have been previouslypublished from individual centres. This study reflects the different histology patternsof renal diseases in children in our centre. OBJECTIVES: To assess the indications for kidney biopsy and determine the different histology patterns of renal diseases in paediatric patients in our centre. SUBJECTS AND METHODS: This retrospective study has been conducted at The Children’s Hospital and The Institute of Child Health Lahore from February 2014 to February 2015. The data has been collected from the renal biopsy record of Paediatric Nephrology department. The paediatric patients of either sex aged less than 16 years diagnosed with renal diseases that required renal biopsy were included in the study. RESULTS: Out of the total of 159 patients, 102(64.2%) were males and 57(35.8%) were females. The age range was 0.7 years to 16 years, mean age= 7.86 years and SD + 4.00. The most common indications for renal biopsy were steroid resistant nephrotic syndrome (SRNS), atypical nephrotic syndrome and lupus (SLE) nephritis.The most common histology reportedwas Mesangioproliferative Glomerulonephritis in 71(44.7%) patients followed by Membranoproliferative Glomerulonephritis in 36(22.6%)whilelupus nephritis was seen in(18)11.4% patients. CONCLUSIONS: The most common indication of renal biopsy was SRNS and the frequent histology reported was Mesangioproliferative Glomerulonephritis. SLE nephritis also prevails in large number of paediatric patients.